2017
DOI: 10.5056/jnm16056
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Excessive Daytime Sleepiness and Functional Gastrointestinal Disorders: A Population-based Study in China

Abstract: Background/AimsSeveral studies have demonstrated that sleep problems are associated with functional gastrointestinal disorders (FGIDs): irritable bowel syndrome (IBS), functional dyspepsia, etc, but the relationship between excessive daytime sleepiness (EDS) and FGIDs has not been systematically studied in the general population. This study aims to explore the relationship between EDS and specific types of FGIDs and the effect of the number of FGIDs on EDS. MethodsA sample of 3600 individuals (aged 18-80 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
0
11
1
Order By: Relevance
“…The link between functional gastrointestinal disorders and deteriorated sleep quality has been well documented in non-CKD adult patients. In population-based study, Wu et al found that excessive daytime sleepiness was significantly associated with increased odds ratio of diarrhea-predominant irritable bowel syndrome (IBS), alternating IBS, and functional constipation in adult Chinese (age in range of 18-80 years) [18]. Interestingly, among French adult patients (mean age 48.2 ± 16.7 years) with functional gastrointestinal disorders, functional constipation and bloating have been associated with insomnia, while functional diarrhea and nonspecific bowel disorders with drowsiness [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The link between functional gastrointestinal disorders and deteriorated sleep quality has been well documented in non-CKD adult patients. In population-based study, Wu et al found that excessive daytime sleepiness was significantly associated with increased odds ratio of diarrhea-predominant irritable bowel syndrome (IBS), alternating IBS, and functional constipation in adult Chinese (age in range of 18-80 years) [18]. Interestingly, among French adult patients (mean age 48.2 ± 16.7 years) with functional gastrointestinal disorders, functional constipation and bloating have been associated with insomnia, while functional diarrhea and nonspecific bowel disorders with drowsiness [17].…”
Section: Discussionmentioning
confidence: 99%
“…Uncovering the manageable causes of sleep disorders in CKD patients would greatly benefit this group of patients. Interestingly, there are factors associated both with CKD and sleep disorders, such as decreased melatonin level, increased body mass index (BMI), and functional constipation [15][16][17][18]. However, the associations between constipation-related symptoms and quality of sleep in CKD patients have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for this difference may lie in the age range of subjects, number of samples, and different evaluation methods to assess psychological and sleep disorders. With epidemiological studies on a large sample in multicenters (subjects: 3600, age: 18–80), Wu et al found that 22.16% of FGIDs suffered excessive daytime sleepiness (EDS) (assessed by Epworth sleepiness score), and the situation is the most severe in ulcer-like dyspepsia and gallbladder dysfunction [ 3 ]. One potential cause of our results that different from the previously study is the index measuring sleep disorder and demographic characteristics of enrolled patients.…”
Section: Discussionmentioning
confidence: 99%
“…The morbidity of FGID in China ranges from 5.67% to 55.24% [ 3 , 4 ]. The previous study showed that besides the digestive system the symptoms were associated with issues in psychological status and sleep disorders [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Impaired sleep quality and chronic fatigue are frequently reported in these patients. Recent data from 3600 Chinese patients with functional gastrointestinal disorders, indicate that excessive daytime sleepiness is present as well 80 .…”
Section: Digestive Diseases and Sleep Disordersmentioning
confidence: 99%